Characteristics of the Detective Novel and Issues of Artistic Interpretation - Niyazov Ravshan Turakulovich (Zien Journals, 2023)
When the detective is considered as the only literature read by the general public, it defines a clear boundary between good and bad, that is, as Joyce Porter noted, "it is characteristic of the detective to raise the issue of the problems of the categories of truth, justice and injustice, but this feature is not observed in other genres". About the generalized formula of the detective, Whiston Hugh Auden writes: "Murder occurs, many suspects, all suspects except for one person who committed the murder are eliminated, the murderer is killed or captured." But this short definition is not perfect enough, it presupposes a different view, which all critics support; it requires a clear order, a clearly defined and sequence of elements of all plot structure, and this shows that the detective story is different from other literary forms
Keywords: detective; defined; sequence; structure